Measuring patients' attitudes to care across the primary/secondary interface: the development of the patient career diary. Issue 3 (1st September 1999) - Baker, R; Preston, C; Cheater, F; Hearnshaw, H
Abstract : BACKGROUND: A growing number of new ways of organising services across the primary/secondary interface are being introduced and evaluated. The principal motive for such reorganisation is to improve the efficiency of health care. However, unless the impact of the new services on patients is investigated and taken into account, it is possible that patients' reactions could be negative, a factor that could lead to unexpected consequences in the use and costs of services. OBJECTIVE: To develop a measure of patients' attitudes towards care across the interface between primary and secondary care. DESIGN: Generation of questions to be included in the measure from a qualitative study of patients' experiences of care across the interface; administration of pilot versions of the measure to samples of patients referred to secondary care; refinement of questions guided by analysis of response patterns, principal components analysis and internal consistency; administration of the final version of the patient career diary in complete form retrospectively to patients referred to secondary care, and one section alone to patients attending outpatient departments for follow up appointments. Face validity was assessed by analysis of open comments in a sample of 50 diaries, and review of the diary by 34 health professionals. Construct validity was assessed by investigation of levels of correlation between components of each section of the diary and the components of the healthcare section overall. SETTING: In the final field test, patients were attending various hospital services, including cardiology, dermatology, neurology, gynaecology, general surgery, general medicine, ophthalmology, trauma and orthopaedics, and gastroenterology. RESULTS: The final version of the diary included 109 questions in seven sections: general practitioner (GP) visits and referral, other GP visits, first outpatient visit, other outpatient visits, inpatient stay and discharge, care after discharge, and care overall. Response rates were poor for retrospective completion of the entire diary, but excellent when a section was given separately. Principal components analysis confirmed that components relating to issues identified as important to patients in the qualitative study had been included in the diary. Levels of internal consistency were good, and comments of patients and health professionals supported validity. CONCLUSION: The patient career diary is a valid and reliable measure of patients' attitudes to care across the interface. It should be given in sections to ensure adequate response rates, and is suitable for use in the evaluation or quality of patterns of care across the interface. In future, the impact on patients of new ways of organising services across the interface should be investigated by use of measures such as the patient career diary.